Additive manufacturing and supply chains – a systematic review. Issue 13 (3rd October 2022) - Kunovjanek, Maximilian; Knofius, Nils; Reiner, Gerald
Abstract: In most supply chains, the application of additive manufacturing (AM) is still far from common. However, various industries ranging from aerospace to consumer goods are investigating its potential to enable the digital value chain. Considering these developments, the research community has supported the adoption of AM in supply chains in many ways. This article contributes to the scientific discourse by systematically reviewing relevant literature depending on industry sector, purpose and supply chain area following the SCOR framework to allow fast access to essential information. The review encompasses 1004 articles, where 141 were subjected to a full-text analysis with argument-specific coding. Findings revealed the predominant AM trends for supply chains, perceived benefits and challenges, and possible applications. Managerial implications based on an overview of (envisioned) applications of AM in different industries are outlined. Additionally, based on a qualitative analysis, gaps in the literature and future lines of research were identified.